2017
DOI: 10.1021/acs.est.7b01330
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Polyester Thin Films at the Nanoscale: Effects of Polyester Structure and Enzyme Active-Site Accessibility

Abstract: Biodegradable polyesters have a large potential to replace persistent polymers in numerous applications and to thereby reduce the accumulation of plastics in the environment. Ester hydrolysis by extracellular carboxylesterases is considered the rate-limiting step in polyester biodegradation. In this work, we systematically investigated the effects of polyester and carboxylesterase structure on the hydrolysis of nanometer-thin polyester films using a quartz-crystal microbalance with dissipation monitoring. Hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 47 publications
3
91
0
Order By: Relevance
“…We have two complementary explanations for the faster and more extensive 13 CO 2 formation from PB*AT than from P*BAT and PBA*T. The first explanation builds on microscale nonuniformity in the adipate-to-terephthalate ratio within the statistical copolyester PBAT, which gives rise to microdomains with adipate-to-terephthalate ratios that deviate from the ratio of the bulk PBAT. Microdomains with higher adipate-to-terephthalate ratios are known to undergo faster enzymatic hydrolysis than those with lower adipate-to-terephthalate ratios ( 18 20 ). The preferential release of adipate and its subsequent mineralization by soil microorganisms are expected to result in faster and more extensive 13 CO 2 release from the variant in which the 13 C-label is in the adipate (that is, PB*AT), as experimentally observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have two complementary explanations for the faster and more extensive 13 CO 2 formation from PB*AT than from P*BAT and PBA*T. The first explanation builds on microscale nonuniformity in the adipate-to-terephthalate ratio within the statistical copolyester PBAT, which gives rise to microdomains with adipate-to-terephthalate ratios that deviate from the ratio of the bulk PBAT. Microdomains with higher adipate-to-terephthalate ratios are known to undergo faster enzymatic hydrolysis than those with lower adipate-to-terephthalate ratios ( 18 20 ). The preferential release of adipate and its subsequent mineralization by soil microorganisms are expected to result in faster and more extensive 13 CO 2 release from the variant in which the 13 C-label is in the adipate (that is, PB*AT), as experimentally observed.…”
Section: Resultsmentioning
confidence: 99%
“…The preferential release of adipate and its subsequent mineralization by soil microorganisms are expected to result in faster and more extensive 13 CO 2 release from the variant in which the 13 C-label is in the adipate (that is, PB*AT), as experimentally observed. Support for this explanation comes from incubations of unlabeled PBAT films with either Rhizopus oryzae lipase or Fusarium solani cutinase (FsC)—two fungal carboxylesterases with distinct hydrolysis mechanisms ( 18 , 21 ). As expected, 1 H NMR spectroscopy revealed that PBAT films that remained after partial enzymatic hydrolysis were enriched in terephthalate, while the released hydrolysis products were enriched in adipate (figs.…”
Section: Resultsmentioning
confidence: 99%
“…The success of PET hydrolysis relies on a balanced combination of suitable enzyme structure and polymer chain flexibility (Zumstein et al, 2017). There are a few factors, relating to the nature of PET, which influence the extent to which it is hydrolyzed.…”
Section: Impact Of Pet Properties On Enzymatic Activitymentioning
confidence: 99%
“…Extensive experimental evidence has demonstrated that both the mobility of the polymer chains and the accessibility of the enzyme's active site are the major factors enabling the biodegradability of PET (25)(26)(27)(28)(29). Enzymatic PET hydrolysis increases with temperature because of a higher probability of surface chains leaving the polymer structure near its glass transition temperature (T g ¼ 65 C), becoming available targets that fit into the active site of PET-degrading enzymes (26).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, most known PET-degrading enzymes come from thermophilic organisms whose optimal activities are near such T g (14)(15)(16)(17)(19)(20)(21)30), or that have been engineered through rational design to increase their thermostability and exceed this critical temperature, thus improving activity toward this substrate (22,(31)(32)(33)(34). On the other hand, a higher accessibility or exposure of the active site on the protein surface for substrate binding is known to increase polyester hydrolysis (29) by compensating for the high T g of some polymers like PET (26). Numerous engineering efforts have successfully exploited the enlargement of the active sites of several PET-degrading enzymes to increase their plastic-degrading activity (35)(36)(37), but in all cases high temperatures are still required for efficient PET hydrolysis.…”
Section: Introductionmentioning
confidence: 99%